2021
DOI: 10.3390/polym13030374
|View full text |Cite
|
Sign up to set email alerts
|

Adamantane Functionalized Poly(2-oxazoline)s with Broadly Tunable LCST-Behavior by Molecular Recognition

Abstract: Smart or adaptive materials often utilize stimuli-responsive polymers, which undergo a phase transition in response to a given stimulus. So far, various stimuli have been used to enable the modulation of drug release profiles, cell-interactive behavior, and optical and mechanical properties. In this respect, molecular recognition is a powerful tool to fine-tune the stimuli-responsive behavior due to its high specificity. Within this contribution, a poly(2-oxazoline) copolymer bearing adamantane side chains was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…By varying the concentration of the solute, it is possible to tune the temperature at which phase separation occurs. In the following paper [ 86 ], the authors exploited this mechanism by modifying poly(2-oxazolines) with an adamantane group. The adamantane moiety formed inclusion complexes with β-cyclodextrin based on the guest–host interactions.…”
Section: Poly(2-oxazoline)s As Stimuli-responsive Polymersmentioning
confidence: 99%
“…By varying the concentration of the solute, it is possible to tune the temperature at which phase separation occurs. In the following paper [ 86 ], the authors exploited this mechanism by modifying poly(2-oxazolines) with an adamantane group. The adamantane moiety formed inclusion complexes with β-cyclodextrin based on the guest–host interactions.…”
Section: Poly(2-oxazoline)s As Stimuli-responsive Polymersmentioning
confidence: 99%
“…Hence unlocking suitable strategies for non-activated ester modification is extremely valuable for the synthetic diversification, upcycling or recycling of both commodity and more specialized polymers. Although the modification of ester groups is typically avoided in post-polymerization modifications due to their poor reactivity, [7,8] several research groups have recently shown the successful transesterification and amidation of polymeric ester groups, as found in polyesters, [9][10][11][12] polyacrylates, [13][14][15][16] polymethacrylates, [17][18][19] and more specialized polypeptides, [1,2] and poly(2-oxazoline)s. [20][21][22][23][24][25] Particularly the use catalysts has flourished, enabling smooth transesterification of various ester substrates. In contrast, amidation of esters suffers from poor reaction kinetics, often requiring long reaction times at elevated temperatures, even in the presence of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…12 This observed heating-induced decomplexation is an intriguing, † Electronic supplementary information (ESI) available. See DOI: https://doi.org/ 10.1039/d2py00219a a School of Chemical Engineering and Technology, Sun Yat-sen University, Zhuhai 519082, China b but rather specific phenomenon as most other kinds of hostguest complexes attached to a thermoresponsive polymer have been reported to retain in the complexed state upon crossing the T cp (e.g., cyclodextrins, [14][15][16] pillararene 17 hosts or terpyridine ligands 18 ). Benefiting from this LCST-induced decomplexation process that is accompanied by the loss of the characteristic color of the donor-acceptor host-guest complex, this reversible temperature-controlled host-guest interaction can serve as an ideal platform for various potential applications, such as targeted molecular release, or thermoresponsive sensors.…”
Section: Introductionmentioning
confidence: 99%